Affirmative action policies for access to higher education: freirean reflections - Feitosa de Carvalho Pedrozo Gonçalves, Monica (2023)
This paper aims to reflect on affirmative action policies for access to higher education basedon the theoretical assumptions of Paulo Freire. The essence of affirmative action policies is to combat allforms of discrimination and to reduce social inequalities, which enabled the dialogue with the theoreticalassumptions of Paulo Freire. We believe that the theoretical guidelines advocated by Freire, based on politicaland liberating consciousness is the driving force for the transformation of society with a view to overcomingsocial inequalities. This article is characterized as a qualitative, bibliographical and exploratory study.